2017
DOI: 10.4314/wsa.v43i1.11
|View full text |Cite
|
Sign up to set email alerts
|

The viability of domestic rainwater harvesting in the residential areas of the Liesbeek River Catchment, Cape Town

Abstract: By 2030 South Africa (SA), a developing country, is predicted to be severely impacted by physical water scarcity. In order to avert a future water crisis, the country needs to find ways to reduce its reliance on conventional surface water schemes based on impoundments on rivers. Rainwater harvesting (RWH) is an alternative water resource. To date, the viability of domestic RWH within an urban setting has not been adequately considered in SA. The purpose of this study was thus to address this omission through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Fisher-Jeffes et al (2017) confirmed that rainwater use, in the Western Cape study area investigated by the team, was not financially viable and underlined the need for future research to better understand the viability of rainwater harvesting in different climatic regions of South Africa.…”
Section: Theoretical Garden Irrigation Demandmentioning
confidence: 77%
“…Fisher-Jeffes et al (2017) confirmed that rainwater use, in the Western Cape study area investigated by the team, was not financially viable and underlined the need for future research to better understand the viability of rainwater harvesting in different climatic regions of South Africa.…”
Section: Theoretical Garden Irrigation Demandmentioning
confidence: 77%
“…This was expected as Fisher-Jeffes [4] showed that SWH systems are most likely to be economically viable when supplying areas with a high water demand concentration (i.e., water demand/area) as this limits the extent of the dual water distribution network required-thereby keeping the infrastructure costs down. Each of the three options that modelled WDA 2 indicated a cost per cubic metre to supply harvested stormwater comparable to the typical maximum tariffs (15.81, 23.51 or 29.03 ZAR/m 3 depending on the demand; the CoCT uses a 'rising-block' tariff scheme) that residents within the catchment were being billed by the CoCT for their potable water usage at the time of the study.…”
Section: Resultsmentioning
confidence: 99%
“…Chlorination, as a method of disinfection, was avoided as chlorinated water can have harmful effects on plants if the water is used for irrigation purposes. Since the required dose of UV disinfection is dependent on the UV transmittance (UVT) of the water, the harvested stormwater would require filtration beforehand to ensure a consistent quality [4]. The inclusion of slow sand filters-a low cost treatment device requiring relatively low levels of maintenance that can tolerate wide fluctuations in flow range whilst still effectively removing organic matter and mild turbidity [56,57]-was assumed for this purpose.…”
Section: Treatment Of Harvested Stormwatermentioning
confidence: 99%
See 2 more Smart Citations